David, Frayne (9 April 2019) The Work Cure: Critical essays on work and wellness (Concept: The Journal of Contemporary Community Education Practice Theory, 2021)
Community and youth workers find themselves working in precarious situations - sessional work, short-term contracts, threats to the services they provide - and at the same time, the people they work with are also in precarious jobs and/or dealing with benefit conditionality in particular those claiming Universal Credit. I am writing this review in the middle of the Covid-19 pandemic, when these existing problems with employment/unemployment cannot be shied away from anymore and when increasing numbers of people are dependent on Universal Credit as well as food banks. There is growing recognition of the important role of not just highly skilled NHS workers but also of cleaners, warehouse workers, drivers, shop workers and social care workers. These are jobs which have long been prone to zero hours contracts, with low rates of both pay and union membership.